Indonesia’s Contribution to Maritime Security and Climate Justice in the Global South - Wibowo, Tri (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2026)
As a prominent maritime power in the Global South, Indonesia holds strategic potential to shape global maritime governance. Through the Global Maritime Axis (GMA) launched in 2014, Indonesia reaffirmed its commitment to safeguarding maritime stability. However, the existing GMA framework remains overly centered on traditional threats such as sovereignty protection and military defense, overlooking the growing impact of non-traditional challenges—particularly those related to climate change. To enhance its maritime resilience, Indonesia’s maritime security framework must evolve to incorporate the climate-security nexus. This study employs a qualitative descriptive-analytical approach to explore the interrelationship between maritime security and climate justice, drawing from nationally and internationally indexed literature. Findings underscore that the ocean's role in regulating the global climate necessitates inclusive, collaborative governance that transcends traditional boundaries. Climate justice, as a normative framework, demands the recognition of shared but differentiated responsibilities, especially for vulnerable maritime nations like Indonesia. Within the context of the Archipelagic and Island States (AIS) Forum, Indonesia has emerged as both an initiator and host, advancing principles of ocean collaboration, innovation, and sustainability. By reconceptualizing maritime security to include environmental protection, equitable resource governance, and marine biodiversity conservation, Indonesia can lead a transformative approach to climate justice. This repositioning enables Indonesia to protect its ecological and geopolitical interests while serving as a model for other developing maritime states. Ultimately, fostering climate resilience through maritime cooperation enhances regional stability and contributes meaningfully to global climate goals.